ПОНЯТТЯ Й СТРУКТУРА КОМПЕТЕНЦІЇ ВЧИТЕЛІВ ОБРАЗОТВОРЧОГО МИСТЕЦТВА (Педагогіка вищої та середньої школи, 2007)
The author make an attempt to define the conception of competence offuture teachers cffine art. The typical scheme of socialindividual andprcfessional-value competences is worked out.